2002
DOI: 10.1183/09031936.02.00229302
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between respiratory tract infections and atopy in the aetiology of asthma: Fig. 1.—

Abstract: The prevalence of asthma, in particular atopic asthma, has markedly increased in recent years. Accumulating evidence suggests that environmental factors associated with allergic sensitization and exposure to microbial stimuli during infancy and early childhood, are associated with these changes in prevalence. However, considerable controversy surrounds the role of microbial agents, as evidence has been presented for both positive and negative effects in this context.The review below focuses upon interactions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 77 publications
2
37
0
1
Order By: Relevance
“…Recent epidemiological studies have indicated that the key events essential for the development of persistent allergic asthma, such as contact with aeroallergens, occur in early childhood (1, 2, 52). There is also mounting evidence that the basis of Th2 memory against these allergens and the subsequent clinical outcome (e.g., the allergic march) are generated during these early years (53)(54)(55). Based on the results of the current study, we propose that the phenotype spread, or a similar mechanism, is responsible for the accelerated development of the allergic/asthmatic phenotype in a susceptible individual in early childhood.…”
Section: Discussionmentioning
confidence: 63%
“…Recent epidemiological studies have indicated that the key events essential for the development of persistent allergic asthma, such as contact with aeroallergens, occur in early childhood (1, 2, 52). There is also mounting evidence that the basis of Th2 memory against these allergens and the subsequent clinical outcome (e.g., the allergic march) are generated during these early years (53)(54)(55). Based on the results of the current study, we propose that the phenotype spread, or a similar mechanism, is responsible for the accelerated development of the allergic/asthmatic phenotype in a susceptible individual in early childhood.…”
Section: Discussionmentioning
confidence: 63%
“…exposure to a wide spectrum of microorganisms from diverse sources). The immunological basis and the mechanisms that are thought to operate in this immunomodulation, have been discussed in detail in several recent reviews and will not be reiterated here (49)(50)(51)(52)(53)(54). In addition, a number of animal experiments have provided support for the hygiene hypothesis (55)(56)(57)(58), but these data are also beyond the scope of this review.…”
Section: The Hygiene Hypothesismentioning
confidence: 98%
“…Several Nod1 polymorphisms have been associated with the development of atopic eczema and asthma, as well as with increased levels of serum IgE in several human populations (60,61). The link between Nod1 and asthma is intriguing in that microbial exposure in childhood is known to protect against the development of disease (62). Thus, it is possible that cytosolic recognition of bacterial products via Nod1 in the skin and mucosal surfaces regulates directly or indirectly Th2 polarization and IgE levels.…”
Section: Nlr Genetic Variants and Human Disease Susceptibilitymentioning
confidence: 99%